Optimization of cardiac CT angiography scistole phase image quality in the right coronary artery with helical segment snapshot method using adaptive statistical iterative reconstruction (ASIR) and temporal resolution enhancement - Akhirida Putri; Mira Maya Kumala (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Optimization of image quality in Cardiac CT Angiography (CCTA) is important for accurate evaluation of the right coronary artery (RCA). This study evaluates the effects of Adaptive Statistical Iterative Reconstruction (ASIR) and Temporal Resolution Enhancement on the image quality of the RCA sistole phase using the helical segment snapshot method. The study involved 10 patients with 40% ASIR reconstruction, 70% ASIR and 70% ASIR + Temporal Resolution Enhancement. Quantitative analysis showed that increasing ASIR levels significantly reduced noise and increased Signal-to-Noise Ratio (SNR). However, the sharpness of ASIR image is 40% higher than ASIR 70% (p < 0.05). The addition of Temporal Resolution Enhancement significantly increased the sharpness of ASIR images by 70% (mean score 4.4; p < 0.05). In conclusion, Temporal Resolution Enhancement effectively optimizes the quality of RCA images in the systole phase, supporting its use in CCTA techniques.